Unveiling greenwashing: Risks in sustainability and ESG reporting - Jamil, Nurul Nazlia; Wahyuni , Ersa Tri (International Journal of Accounting, Finance and Business, 2024)
In recent years, the corporate world has witnessed a surge in sustainability reporting, reflecting a growing awareness of environmental and social responsibility. However, amidst this trend lies a significant risk of greenwashing. Greenwashing refers to the deceptive practice of conveying a false impression or providing misleading information about a company's environmental efforts. This paper explores the phenomenon of greenwashing and its ramifications in sustainable reporting. Companies often resort to superficial gestures or cosmetic changes to portray themselves as environmentally conscious, while their core operations remain unchanged. The paper also examines the implications of greenwashing on stakeholders and the environment. Misleading sustainability reporting can erode trust among consumers, investors, and communities, leading to reputational damage and financial losses. The study is employing an inductive approach which analysing literature to develop coherent narratives and theoretical insights regarding the phenomenon of greenwashing and its implications for sustainability reporting. The study makes attempts to highlight the challenges in detecting and combating greenwashing. With the lack of standardized metrics and regulatory oversight, distinguishing between authentic sustainability practices and deceptive claims becomes increasingly difficult. This opacity poses risks not only to stakeholders but also to the credibility of sustainability reporting as a whole. The paper concludes the need for increasing integration of ESG metrics into business practices, the innovative approaches in ESG practices and the shift towards risk management can minimize the greenwashing activities. In conclusion, this paper underscores the importance of addressing greenwashing to foster genuine progress towards sustainability. By embracing these changes and viewing ESG as an integral part of their strategy, companies can not only fulfil their ethical obligations but also unlock new opportunities for growth and resilience.